2016
DOI: 10.1002/epi4.2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of carbamazepine in the intrahippocampal kainate model of temporal lobe epilepsy depend on seizure definition and mouse strain

Abstract: SummaryObjectiveMesial temporal lobe epilepsy (TLE) with hippocampal sclerosis is a predominant form of acquired epilepsy, characterized by recurrent simple and complex partial seizures that are often resistant to treatment. Mice developing spontaneous recurrent nonconvulsive and convulsive seizures after intrahippocampal injection of the excitotoxic glutamate agonist kainate are thought to represent a valuable model of mesial TLE. Epileptic electroencephalogram (EEG) activity recorded in this model from the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 56 publications
(195 reference statements)
6
53
0
Order By: Relevance
“…Knowledge of paroxysmal EEG activity in otherwise “normal” mice that are used as experimental controls is important because it may interfere with epilepsy or seizure models using such mouse strains. In outbred mouse strains such as NMRI or Swiss, no SWDs have been observed [100-102]. …”
Section: Interstrain Differences In the Expression Of Seizures Andmentioning
confidence: 99%
See 3 more Smart Citations
“…Knowledge of paroxysmal EEG activity in otherwise “normal” mice that are used as experimental controls is important because it may interfere with epilepsy or seizure models using such mouse strains. In outbred mouse strains such as NMRI or Swiss, no SWDs have been observed [100-102]. …”
Section: Interstrain Differences In the Expression Of Seizures Andmentioning
confidence: 99%
“…In a subsequent study, we found that the mouse strain also affected the occurrence of different types of spontaneous electrographic seizures and their pharmacological sensitivity in this model [102]. The typical electrographic seizures observed in epileptic mice are high- voltage sharp waves (HVSWs) and hippocampal paroxysmal discharges (HPDs) [100-102].…”
Section: Interstrain Differences In the Expression Of Seizures Andmentioning
confidence: 99%
See 2 more Smart Citations
“…This prompted us to perform a prospective study in which EEG alterations occurring in this model were compared with the EEGs in appropriate sham controls, using hippocampal electrodes and video‐EEG monitoring. For this study we chose male mice of the NMRI (Naval Medical Research Institute) outbred strain, a general‐purpose strain in many fields of biology as well as in pharmacology and toxicology, which was previously used for this model by our group and others . We expect that our study adds to the current discussion about how to best define a “seizure” in experimental models of acquired epilepsy and how careful study of control animals can clarify this issue .…”
mentioning
confidence: 99%